The Influence of Product Quality, Brand Image and Promotion on Financing Decision with Customer Interest as Mediating Variable - Rusmiyati Rusmiyati; Sri Hartono (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2022)
The competition of consumer finance companies is increasing. This condition is beneficial for consumers due to many choices from finance companies. This study was structured to analyze the effect of brand image, product quality, and promotion on financing decisions mediated by customer interest. The population was customers of company XXY of 2.810 people in Jabodetabek, with a total sample of 130 respondents selected using simple random sampling. Data analysis applied Partial Least Square (Smart-PLS) version 3.0. The results proved that brand image, product quality, and promotion had a positive and significant impact on customer interest and financing decisions. In addition, it is concluded that customer interest can mediate the influence of brand image, product quality, and promotion on customer financing decisions. Therefore, it is recommended that the company prepare customer education steps regarding the benefits or benefits obtained if they decide to use the company as a means of financing.